2010
DOI: 10.1111/j.1744-7402.2010.02508.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Ring‐on‐Ring Equibiaxial Flexural Strength of Borosilicate Glass

Abstract: A novel dynamic ring‐on‐ring equibiaxial flexural testing technique with single pulse loading capability is established on a modified Kolsky bar. This technique is then utilized to investigate the loading‐rate and surface‐condition effects on the flexural strength of a borosilicate glass. Quasi‐static and dynamic experiments are performed at loading rates ranging from 5 × 10−1 to 5 × 106 MPa/s. It is found that the flexural strength of the borosilicate glass strongly depends on the applied loading rates. HF ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…The validity of Eq. 5 is limited to a certain level of applied stress rates where the bending strength no longer increases with increasing stress rate [23,24]. In the current investigation, the loading rates appear to be too low to expect that the values get close to such an inert strength even at the highest used loading rates.…”
Section: Resultsmentioning
confidence: 81%
“…The validity of Eq. 5 is limited to a certain level of applied stress rates where the bending strength no longer increases with increasing stress rate [23,24]. In the current investigation, the loading rates appear to be too low to expect that the values get close to such an inert strength even at the highest used loading rates.…”
Section: Resultsmentioning
confidence: 81%
“…This can be due to the higher 579 failure strain of glass under dynamic loading. Nie et al (2010) found that depending on the 580 surface condition of the glass, dynamic failure strain can be five times greater than its quasi-581 static value. The strain at location 2 is compared in Fig.…”
Section: -2 the Effect Of The Nose Shape Of The Projectile 524mentioning
confidence: 99%
“…For this reason, the edges were not further chamfered after flame polishing to avoid introducing new strength-limiting flaws. Results from previous room temperature equibiaxial ring-on-ring tests on the same material have revealed that the well-polished samples failed from pre-existing surface cracks [17], due to the fact that the flaws introduced by mechanical contact (grinding, polishing etc.) are dominant on the glass surface.…”
Section: Materials and Specimensmentioning
confidence: 97%
“…Recently, novel modifications to this wellrecognized apparatus have expanded its capability to the testing of a broader range of materials such as armor ceramics [16,19] and biological tissues [20,21]. The study in [17] described the implementation of ring-on-ring equibiaxial loading fixtures and single loading capabilities to a conventional Kolsky bar. For this new version of the Kolsky bar, the dynamic flexural strength of borosilicate glass was characterized with different surface modifications.…”
Section: Materials and Specimensmentioning
confidence: 98%
See 1 more Smart Citation